Kesetaraan Perempuan dalam masyarakat adat suku moi kota sorong - Ahdiyanti, Istika (SOSIORELIGIUS, 2025)
The Moi people are one of the ethnic groups originating from Papua, Indonesia. The Moi people live in a relatively remote area, where their traditions and social structures have developed in distinctive and diverse ways, depending on the social and geographical environment. When discussing gender equality within their society, there are several aspects that need to be understood, both in terms of tradition and changes that have occurred due to external influences. This study uses a qualitative method of in-depth interview techniques with parties related to the research theme. The results show that, Gender equality in the Moi people, as in many other indigenous communities, exists in a complex context between tradition and social change. Although the roles of women and men are usually different and limited by cultural norms, there is room for complementarity and appreciation of the contributions of both. On the other hand, with the influence of education and modernization, women in the Moi people have also begun to access new opportunities, which allow them to have more voice and role in society.